2010
DOI: 10.1073/pnas.1000956107
|View full text |Cite
|
Sign up to set email alerts
|

Heme biosynthesis is coupled to electron transport chains for energy generation

Abstract: Cellular energy generation uses membrane-localized electron transfer chains for ATP synthesis. Formed ATP in turn is consumed for the biosynthesis of cellular building blocks. In contrast, heme cofactor biosynthesis was found driving ATP generation via electron transport after initial ATP consumption. The FMN enzyme protoporphyrinogen IX oxidase (HemG) of Escherichia coli abstracts six electrons from its substrate and transfers them via ubiquinone, cytochrome bo 3 (Cyo) and cytochrome bd (Cyd) oxidase to oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 40 publications
1
79
0
Order By: Relevance
“…TCA is the prime pathway to generate the majority of reducing equivalents (i.e., NADH in cell) and generates the proton motive force or membrane potential across the membrane essential for ATP synthesis (Möbius et al, 2010). Our results indicate that plumbagin treatment significantly repressed TCA and the electron transport chain, which indicates the blockage in energy generation.…”
Section: Discussionmentioning
confidence: 62%
“…TCA is the prime pathway to generate the majority of reducing equivalents (i.e., NADH in cell) and generates the proton motive force or membrane potential across the membrane essential for ATP synthesis (Möbius et al, 2010). Our results indicate that plumbagin treatment significantly repressed TCA and the electron transport chain, which indicates the blockage in energy generation.…”
Section: Discussionmentioning
confidence: 62%
“…The latter molecule is a primary electron carrier in the respiratory electron transport chain. Heme auxotrophy is believed to exert its influence on colony size (and bacterial doubling time) via the loss of respiration-associated cytochromes and terminal reductases (69). We therefore compared the ⌬hemQ and hemB growth phenotypes in the liquid phase under aerobic and anaerobic (fermentative) conditions, observing significantly slowed growth and attenuated final culture densities for the mutants specifically in the aerobic case (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HemG activity is indirectly coupled to respiration. In Escherichia coli it has been suggested that HemG activity also has a direct role in respiration (59,60). At this stage, it is unclear how the specific hemG mutations identified provide resistance to IS-INP0341.…”
Section: Discussionmentioning
confidence: 99%